ACCOALTIC: Bottom loading dispenser through raw water source Kuantan River polluted Hg from unlicensed gold mining activity - Lidia Mubarak; Nurfi Hikma; Elda Juliana Jelita; Marsya Rizkya Ramadhani; Najwa Az-Zuhra; Muhammad Dino Septama; Muhammad Fadhil (Science, Technology, and Communication Journal, 2025)
Unlicensed gold mining activities are still a polemic in the people of Kuantan Singingi Regency, starting from 2006 until now. Kuantan River water has a turbidity of 72.42 NTU, a concentration of 0.0325 mg/l Hg, and a bacterial count of 410 CFU/100 ml. Eventhough, Kuantan River water is the main source of raw water used by UPTD PAB with 3,727 active customers. Until now, water treatment at UPTD still uses alum as a purifier without laboratory-scale analysis. The purpose of this study is to analyze the effectiveness of ACCOALTIC's working principles in the Kuantan River raw water purification process and explain the results of the development of ACCOALTIC bottom loading dispenser. The study was conducted in quantitative experiments. ACCOALTIC uses the working principle of 3 filtration tanks, namely purification & coagulation, adsorption, and disinfection. Test parameters using a turbidity meter get an average value of 5 tests per sample after treatment of 0.1 NTU. The decline occurs due to the nature of Al2(SO4)3 contains aluminum sulfate. In the XRD test of Hg absorption, there is a peak in the X-ray intensity coordinates (a.u.) which indicates the presence of Hg. SSA testing found a decrease in Hg concentration by 77.21%. The number of E. coli bacteria was 410 (before treatment) and 2 (before treatment) in CTU/100 mL units, hence the % value decreased by 99.51% while the development of ACCOALTIC is carried out in the form of bottom loading dispensers.